Enhancing diesel engine performance, combustion, and emissions reductions under the effect of cerium oxide nanoparticles with hydrogen addition to biodiesel fuel - Polat, Fikret; Saridemir, Suat; Gad, M. S.; El-Shafay, A. S.; Agbulut, Umit (PERGAMON-ELSEVIER SCIENCE LTD, 2024)
In order to enhance engine combustion and emissions, inclusion of nano additives containing hydrogen is recommended due to the high viscosity, poor calorific value, atomization, and vaporization issues of biodiesel. Transesterification was used to transform sunflower oil into methyl ester. Sunflower biodiesel of 20% by volume was blended with diesel fuel, and CeO2 nanoparticles of 100 ppm were added to blends. Hydrogen was introduced by 5 and 10 lpm from intake manifold. Diesel engine operated at 2000 rpm and loads of 15, 30, 45, and 60 N m. BSFC was decreased by 1.77%, 4.71%, and 7.19% but BTE was improved by 1.39%, 4.04%, and 7.01% when cerium oxide, 5, and 10 lpm hydrogen were added to B20, respectively. When methyl ester mixture was combined with nano additive and H2 at 5 and 10 lpm, respectively, EGT was reduced by 2.62, 4.77, and 6.73%. B20+ CeO2 and B20+ CeO2+ 5 lpm, and B20+ CeO2+ 10 lpm showed decreases of 46.51%, 56.59%, and 63.57% in CO emissions but the declines in NOx were 6.34, 13.6% and 20.71%, respectively compared to diesel oil. Inclusion of nano-doped hydrogen at 5 and 10 lpm reduced HC emissions by 12.09% and 28.57%, respectively, about diesel. Hydrogen addition of 5 and 10 lpm to CeO2-doped B20 improved the in-cylinder pressures by 3% and 3.52% but the maximum heat release rate increases were 3% and 3.52% respectively compared to diesel. Biodiesel from sunflower oil with 100 ppm CeO2 with hydrogen shows reductions in emissions and combustion enhancement.
Keywords: Biodiesel; Cerium oxide nanoparticles; Hydrogen; Engine performance; Combustion characteristics; Emissions; COMPRESSION IGNITION ENGINE; OIL; BLENDS; ENERGY; Chemistry; Electrochemistry; Energy & Fuels